Effects of phenyl acids on different degradation phases during thermophilic anaerobic digestion - Prem, Eva Maria; Schwarzenberger, Alessa; Markt, Rudolf; Wagner, Andreas Otto (Frontiers in Microbiology, 2023)
Aromatic compounds like phenyl acids (PA) can accumulate during anaerobic digestion (AD) of organic wastes due to an increased entry of lignocellulose, secondary plant metabolites or proteins, and thermodynamic challenges in degrading the benzene ring. The effects of aromatic compounds can be various - from being highly toxic to be stimulating for methanogenesis - depending on many parameters like inoculum or molecular characteristics of the aromatic compound. To contribute to a better understanding of the consequences of PA exposure during AD, the aim was to evaluate the effects of 10 mM PA on microbial communities degrading different, degradation phase- specific substrates in thermophilic batch reactors within 28 days: Microcrystalline cellulose (MCC, promoting hydrolytic to methanogenic microorganisms), butyrate or propionate (promoting syntrophic volatile fatty acid (VFA) oxidisers to methanogens), or acetate (promoting syntrophic acetate oxidisers to methanogens). Methane production, VFA concentrations and pH were evaluated, and microbial communities and extracellular polymeric substances (EPS) were assessed. The toxicity of PA depended on the type of substrate which in turn determined the i) microbial diversity and composition and ii) EPS quantity and quality. Compared with the respective controls, methane production in MCC reactors was less impaired by PA than in butyrate, propionate and acetate reactors which showed reductions in methane production of up to 93%. In contrast to the controls, acetate concentrations were high in all PA reactors at the end of incubation thus acetate was a bottle-neck intermediate in those reactors. Considerable differences in EPS quantity and quality could be found among substrates but not among PA variants of each substrate. Methanosarcina spp. was the dominant methanogen in VFA reactors without PA exposure and was inhibited when PA were present. VFA oxidisers and Methanothermobacter spp. were abundant in VFA assays with PA exposure as well as in all MCC reactors. As MCC assays showed higher methane yields, a higher microbial diversity and a higher EPS quantity and quality than VFA reactors when exposed to PA, we conclude that EPS in MCC reactors might have been beneficial for absorbing / neutralising phenyl acids and keeping (more susceptible) microorganisms shielded in granules or biofilms.